Analysis of Personal Exposure to Particulate Matter 2.5 and Subjective Respiratory Diseaseamong Mechanical Test Officers - Indriani, Aisyah; Kurniati, Anisa; Ramdhan, Doni Hikmat (KnE Life Sciences, 2018)
Exposure to particulate matter 2.5 (PM2.5) in both the short and long term is known to result indeath by respiratory diseases. This study aimed to measure personal exposure concentrations to PM2.5 and the percentage of subjective respiratory complaints frommechanics in the Vehicle Testing Centre (VTC) unit Ujung Menteng in 2015. This study was a descriptive study that measured the personal exposure concentration of PM2.5 during working hours; it used personal sampling equipment, such as theLeland Legacy pumpand the Sioutas Cascade Impactor. The research subjects were 21 mechanical test officers. The results showed that the average personal exposure concentration of PM2.5 experienced by mechanical test officers amounted to 272.35µm/m3 , and 90.5% ofthe mechanical test officers experienced respiratory complaints with the most common complaints being nasal congestion (76.2%) and a sore throat (57.1%). The highest average exposures to PM2.5 that were experienced by the mechanical test officers were in mechanical testing area 2, which was the testing area for heavy vehicles.